The effect of gender and anthropometrical parameters on dynamic of sprint start among young elite sprinters - Ilbeigi, S.; Yousefi, M.; Nasirzadeh, A.; Van Gheluwe, B. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The sprint start is a complex motor task characterized by large forces exerted in the horizontal direction and ability to generate these forces in a short time. The aim of this research was to study the starting block dynamics parameters during the sprint start. Moreover, gender and anthropometrical measurements as corrected thigh girth (CTG), corrected calf girth (CCG) and total body skeletal muscle mass (SMM) were used to evaluate their influence on the dynamic variables. The results presented a significant influence of age, gender and other anthropometrical parameters on block velocity, block acceleration, force and impulse, where the older boys displayed significantly higher block variable values than girls. Moreover, the maximum force exerted on the front and rear legs were the best predictor for the mean velocity of the sprinters.